Unveiling Resilience: Key Factors Shaping the Survival of Bandung's Muslim Fashion Industry During the COVID-19 Era - Asih, Vemy Suci (Indonesian Journal of Economics and Management, 2024)
The covid-19 pandemic has had an impact on various business sectors, including the Muslim fashion industry in the city of Bandung. When many businesses experienced business setbacks, Muslim fashion was able to survive through the covid-19 pandemic. The purpose of this study is to find out what are the factors that affect the Muslim fashion industry through the covid-19 pandemic in the Bandung City area. The method used in this study is quantitative, with factor analysis techniques. The variables used in this study are human resources, innovation, digital marketing, service quality, design, and price. Data was obtained from the results of the distribution of questionnaires filled in by respondents. The sample used in the study was 22 respondents, namely entrepreneurs engaged in Muslim fashion in the Bandung area, West Java, Indonesia. The characteristics of the sample used are, entrepreneurs in the Muslim fashion sector, have a place of business in the Bandung area, the business has been running at least from 2018 to 2021, this business has online and offline stores. The results of this study show that there are two factors that have a positive effect on the resilience of the Muslim fashion industry. The first factor is human resources, service quality, and design. The second factor is innovation, creativity, and digital marketing.